HUBUNGAN KEPATUHAN PENGGUNAAN APD DAN PERILAKU K3 MENINGKATKAN KINERJA KARYAWAN - Erika Afan; Edison Sembiring Cholia; Soehatman Ramli; Sugiarto Sugiarto (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study aims to determine the relationship between compliance with the use of Personal Protective Equipment(PPE) and K3 behavior on employee performance at PT. Enam Prakarsajaya Mandiri. The research method used is quantitative research with a cross-sectional approach. The population used is employees of PT. Enam Prakarsajaya Mandiri, the sample used by 123 respondents through the sampling method used, namely the sampling technique with certain considerations. The analysis technique used is SPSS 25. The results of this study show that there is a relationship between K3 behavior and compliance with PPE use on employee performance. This research will be an input for PT. Enam Prakarsajaya Mandiri continues to be committed to improving the quality of K3 training and facilities to achieve good K3 behavior and compliance with the use of PPE. Because of the high behavior of K3 and compliance with the use of good PPE will improve employee performance which is the ticket to the success of all businesses.